2021
DOI: 10.1021/acschembio.1c00052
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen–Nitrogen Bond Formation Reactions Involved in Natural Product Biosynthesis

Abstract: Construction of nitrogen–nitrogen bonds involves sophisticated biosynthetic mechanisms to overcome the difficulties inherent to the nucleophilic nitrogen atom of amine. Over the past decade, a multitude of reactions responsible for nitrogen–nitrogen bond formation in natural product biosynthesis have been uncovered. On the basis of the intrinsic properties of these reactions, this Review classifies these reactions into three categories: comproportionation, rearrangement, and radical recombination reactions. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 76 publications
1
36
0
Order By: Relevance
“…CNQ-766, they found all carbons of both A80915C 313 and azamerone 286 originated from acetate, except the methyl group of C-8, which is instead methionine-derived. The results also revealed that both the naphthoquinone unit of 313 and the phthalazinone unit of 286 display two distinct 13 C-labeling patterns, consistent with the outcome from feeding studies for napyradiomycins biosynthesis in actinomycete Chainia rubra. 248 These data together suggest that phthalazinone unit of azamerone would be derived from symmetrical pentaketide 1,3,6,8tetrahydroxynaphthalene (THN, 311) and two isoprenoid moieties originated from the mevalonate pathway (Fig.…”
Section: Biosynthesis Of Pyridazinessupporting
confidence: 75%
“…CNQ-766, they found all carbons of both A80915C 313 and azamerone 286 originated from acetate, except the methyl group of C-8, which is instead methionine-derived. The results also revealed that both the naphthoquinone unit of 313 and the phthalazinone unit of 286 display two distinct 13 C-labeling patterns, consistent with the outcome from feeding studies for napyradiomycins biosynthesis in actinomycete Chainia rubra. 248 These data together suggest that phthalazinone unit of azamerone would be derived from symmetrical pentaketide 1,3,6,8tetrahydroxynaphthalene (THN, 311) and two isoprenoid moieties originated from the mevalonate pathway (Fig.…”
Section: Biosynthesis Of Pyridazinessupporting
confidence: 75%
“…The biosynthetic strategies for constructing N-N bonds in natural products have received great attention over the past decade 13 , 14 , 24 , 25 . Despite that there is an increasing number of dedicated enzymes from different protein families that were discovered to be responsible for the formation of N-N linkages in various natural products, little is known about their catalytic mechanism 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Although hundreds of these molecules have also been isolated from nature (Fig. 1a ), the biosynthetic enzymes that are responsible for constructing those unusual N-N bonds, including hydrazine, diazo, and N -nitroso moieties, are only starting to be uncovered very recently 2 14 . Among them, the piperazate synthase KtzT is a heme-dependent enzyme that catalyzes N-N cyclization of l - N 5 -OH-ornithine to give the hydrazine-bearing piperazate, which is a nonproteinogenic amino acid building block for many non-ribosomal peptides 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Although the N–N bond has a relatively small dissociation energy of 240 kJ/mol, this value is only 20% smaller than that corresponding to the C–N bond, which is the next weakest link existing in the proposed system [ 53 ]. In addition, it is worth mentioning at this point that over the last few years, plenty of reactions capable of forming the nitrogen−nitrogen bond in natural product biosynthesis have been revealed, overcoming the technical difficulties due to the inherent nucleophilic nature of nitrogen elements [ 54 ]. Moreover, some nitrogen–nitrogen-bond-containing bioactive products have already been used in clinical practice, evidencing their promising long-life capabilities [ 54 ].…”
Section: Proposed Drug Delivery Systemmentioning
confidence: 99%